2015
DOI: 10.1071/wf13209
|View full text |Cite
|
Sign up to set email alerts
|

Driving factors of fire density can spatially vary at the local scale in south-eastern France

Abstract: South-eastern France is the most wildfire-prone region of the country. To identify the main driving factors in fire density (defined as the number of fires per hectare) at the local scale (clusters of communities that are homogeneous in terms of land cover, climate and wildland–urban interface (WUI)) and to assess their spatial variation at this scale, fire density was investigated in the département Bouches du Rhône using geo-referenced fire ignitions. To assess relationships between fire density and explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Our findings, documented on a large (national) scale, are in line with previous local studies affirming that as the distance to roads, urban settlements, and built-up areas increases, fire occurrence decreases (e.g., [36,41,42,[45][46][47][48][50][51][52][53]55,56,76]), and fire incidence increases (e.g., [54,77]). In the examined case, nearly 50% of fire occurrence and 36% of recurrent fires occurred within 200 m from built-up areas.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings, documented on a large (national) scale, are in line with previous local studies affirming that as the distance to roads, urban settlements, and built-up areas increases, fire occurrence decreases (e.g., [36,41,42,[45][46][47][48][50][51][52][53]55,56,76]), and fire incidence increases (e.g., [54,77]). In the examined case, nearly 50% of fire occurrence and 36% of recurrent fires occurred within 200 m from built-up areas.…”
Section: Discussionsupporting
confidence: 92%
“…Topographic factors have an indirect impact on the occurrence and spread of wildfires by affecting microclimates in local areas. Studies have shown that the topography has a certain impact on the occurrence of wildfires, and wildfires occur more frequently especially in arid sunny slopes, on ridges and in low altitude areas [37]. In this paper, the elevation has a greater impact than do the slope or aspect.…”
Section: Discussionmentioning
confidence: 71%
“…The study area (total surface area of 11 157 km 2 ) is one of the most fire-prone regions of southeastern France in terms of fire frequency (i.e., number of fires) and burned area (Ganteaume and Jappiot, 2013; Ganteaume and Guerra, 2018). The western part is characterized by an extensive WUI where the ignitions are the most frequent (47 % of the total ignitions occurred in the WUI) (Ganteaume and Long-Fournel, 2015). Most large fires occur in summer but their cause is often unknown and when it is known, these large fires are mainly due to arson (Ganteaume and Guerra, 2018).…”
Section: Study Areamentioning
confidence: 99%